Treatment of High Flow Arteriovenous Fistulas after Successful Renal Transplant Using a Simple Precision Banding Technique - Gkotsis, Georgios; Jennings, William C; Malik, Jan; Mallios, Alexandros; Taubman, Kevin (Annals of vascular surgery, 2016)
BACKGROUND: Observation versus ligation of a functional arteriovenous fistula (AVF) after successful renal transplantation (SRT) has been a controversial topic of debate. Congestive heart failure and pulmonary hypertension are common in dialysis patients, and more frequent when vascular access flow is excessive. Renal transplant failure may occur in up to 34% of patients after 5 years, therefore maintaining a moderate flow AVF appears warranted. We review SRT patients with high flow-AVFs (HF-AVF) and clinical signs of heart failure where a modified precision banding procedure was used for access flow reduction. METHODS: Patients referred for HF-AVF evaluation after SRT were identified and records reviewed retrospectively. In addition to recording clinical signs of heart failure, each patient had ultrasound AVF flow measurement before and after temporary AVF occlusion of the access by digital compression. Pulse rate and the presence or absence of a cardiac murmur was noted before and after AVF compression. Adequacy of access flow restriction was evaluated intraoperatively using ultrasound flow measurements, adjusting the banding diameter in 0.5 mm increments to achieve the targeted AVF flow. RESULTS: Twelve patients were evaluated over a 19-month period. Eight (66%) were male and one (8%) obese. Ages were 15-73 years (mean = 42). The AVFs were established 24-86 months previously. The mean pulse rate declined after AVF compression from 90/min to 72/min (range 110-78). Six patients had a precompression cardiac flow murmur that disappeared with temporary AVF compression. One patient with poor cardiac function underwent immediate AVF ligation with dramatic improvement in cardiac status. All other patients underwent a precision banding procedure with real-time flow monitoring. Mean access flow was 2,280 mL/min (1,148-3,320 mL/min) before access banding and was 598 mL/min (481-876) after flow reduction. The clinical signs of heart failure disappeared in all patients. All AVFs remained patent although one individual later requested ligation for cosmesis. Two patients had renal transplant failure and later successfully used the AVF. Follow-up postbanding was 1-18 months (mean = 12). CONCLUSIONS: Patients with successful renal transplants and HF-AVFs had resolution of heart failure findings and maintenance of access patency using a modified precision banding procedure. Flow reduction in symptomatic renal transplant patients with elevated access flow is recommended. Further study is warranted to substantiate these recommendations and clarify the appropriate thresholds for such interventions.
Keywords: Ligation; arteriovenózní zkrat; Male; hemodynamika; Regional Blood Flow; Treatment Outcome; Time Factors; lidé středního věku; retrospektivní studie; Kidney Transplantation; Kidney Diseases; časové faktory; transplantace ledvin; Humans; Blood Flow Velocity; Middle Aged; senioři; rizikové faktory; mužské pohlaví; reoperace; Female; mladiství; Aged; Reoperation; ženské pohlaví; Retrospective Studies; Arteriovenous Shunt, Surgical; regionální krevní průtok; mladý dospělý; Adult; ligace; nemoci ledvin; Young Adult; Hemodynamics; Heart Failure; srdeční selhání; Adolescent; dialýza ledvin; dospělí; lidé; rychlost toku krve; Renal Dialysis; Risk Factors; výsledek terapie